2012
DOI: 10.1002/jcla.21510
|View full text |Cite
|
Sign up to set email alerts
|

Prolidase and Oxidative Stress in Chronic Hepatitis C

Abstract: Background Hepatitis C infection represents a common healthcare issue worldwide. The present trial was designed to investigate the role of prolidase, an enzyme that is significantly involved in the biosynthesis of collagen, and of the oxidative stress that is considered to be involved in the pathogenesis of various diseases, in the chronic hepatitis C infection. The trial was performed to assess the serum prolidase enzyme level and the oxidative–antioxidative status and to determine the relation between the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
1
22
1
1
Order By: Relevance
“…Moreover, there are few studies that have revealed a correlation between the serum prolidase levels and stage of liver fibrosis according to the results of liver biopsy [24,[28][29][30] . In contrast, Duygu et al [22,23] did not observe a relationship between the degree of liver fibrosis and serum prolidase levels in patients with chronic hepatitis B and C. In this study, we observed a significant difference when the prolidase levels in cirrhosis patients were compared with patients with HCC. This might indicate enhanced turnover of collagen synthesis in patients with HCC, which can be affected by the degree of neoplastic transformation during the development of HCC, on the basis of the cirrhotic process.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Moreover, there are few studies that have revealed a correlation between the serum prolidase levels and stage of liver fibrosis according to the results of liver biopsy [24,[28][29][30] . In contrast, Duygu et al [22,23] did not observe a relationship between the degree of liver fibrosis and serum prolidase levels in patients with chronic hepatitis B and C. In this study, we observed a significant difference when the prolidase levels in cirrhosis patients were compared with patients with HCC. This might indicate enhanced turnover of collagen synthesis in patients with HCC, which can be affected by the degree of neoplastic transformation during the development of HCC, on the basis of the cirrhotic process.…”
Section: Discussioncontrasting
confidence: 88%
“…In another study, Myara et al [11] demonstrated increased prolidase activity in chronic liver disease. Elevated prolidase levels in some common conditions, such as hepatitis B infection, hepatitis C infection, nonalcoholic steatohepatitis and alcoholic liver disease, which cause hepatic damage and hepatic fibrosis, have also been reported previously [22][23][24][25] . Although numerous non-invasive markers have been described that predict the severity of hepatic fibrosis [26] , liver biopsy remains a gold standard method for assessing the severity of liver fibrosis and cirrhosis [27] .…”
Section: Discussionmentioning
confidence: 67%
“…Duygu et al suggested that the values of prolidase and the oxidative stress are increased while the antioxidant levels are decreased in chronic hepatitis C and they proposed that prolidase enzyme and oxidative damage might have an association with the HCV infection becoming chronic (35).…”
Section: Oxidative Stress and Prolidasementioning
confidence: 99%
“…9 Prolidaz (E.C.3.4.13.9) kollajen biyosentezinde rol alan matriks metalloproteinaz ailesine dahil bir enzimdir. 10 Prolidaz aktivitesi, plazma, eritrosit ve lökositlerde, hem de karaciğer hastalıkları, 10 …”
Section: Introductionunclassified